Substituted ε iron oxide magnetic particle powder, method for producing substituted ε iron oxide magnetic particle powder, powder compact, method for producing powder compact, and radio wave absorber
A novel production method for ε iron oxide magnetic particle powder reduces α-type iron-based oxides to less than 3% by using a silicon compound coating at specific pH levels, improving radio wave absorption and magnetic recording performance.
Patent Information
- Application Number
- CN202080018538.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-09-30
- Filing Date
- 2020-02-28
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2040-02-28
AI Technical Summary
Existing methods for producing ε-Fe2O3 and ε-type iron oxides result in a significant content of non-magnetic α-type iron-based oxides as impurities, which hinder their effectiveness as radio wave absorbers and magnetic recording media due to reduced radio wave absorption properties and recording density.
A production method involving the use of a silicon compound with a hydrolyzable group added to a precursor solution at a pH of 2.0 to 7.0, followed by neutralization to a pH of 8.0 to 10.0, and aging to form a uniform coating, reduces the α-type iron-based oxide content to less than 3%.
The method produces substitutional ε iron oxide magnetic particle powder with improved radio wave absorption and magnetic recording capabilities by minimizing α-type iron-based oxides, enhancing thermal stability and coercivity control.
Smart Images

Figure CN113508442B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to substitutional ε iron oxide magnetic particle powder suitable for high-density magnetic recording media, radio wave absorbers, etc., and in particular, to substitutional ε iron oxide magnetic particle powder having a reduced content of non-magnetic α-type iron-based oxides that are a different phase from substitutional ε iron oxide, and a method for producing the same. In this specification, oxides formed by substituting a part of the Fe sites of ε-Fe2O3 with other metal elements are referred to as ε-type iron-based oxides, and substitutional α-iron oxide particles having the same crystal system as that of α-Fe2O3 are referred to as α-type iron-based oxides. Background Art
[0002] ε-Fe2O3 is a very rare phase even in iron oxide. At room temperature, nano-sized particles show a conductivity of 20 kOe (1.59×10 6 A / m), so a method for synthesizing ε-Fe2O3 in a single phase has been discussed in the past (Patent Document 1). However, when ε-Fe2O3 is used for magnetic recording media, there is currently no corresponding magnetic head material with a high level of saturation flux density. Therefore, in actual use, it is necessary to replace a part of the Fe sites of ε-Fe2O3 with trivalent metals such as Al, Ga, and In and adjust the coercive force. When used as an electromagnetic wave absorbing material, it is also necessary to change the replacement amount of the Fe sites according to the required absorption wavelength (Patent Document 2).
[0003] On the other hand, the magnetic particles of ε-type iron oxides are very fine. Therefore, in order to improve environmental stability and thermal stability, it is also studied to replace part of the Fe sites of ε-Fe2O3 with other metals with excellent heat resistance. x B y Fe 2-x-y O3 or ε-A x B y C z Fe 2-x-y-z Various partial substitution forms of ε-Fe2O3 with excellent environmental stability and heat resistance represented by O3 (wherein A is a divalent metal element such as Co, Ni, Mn, Zn, etc., B is a tetravalent metal element such as Ti, and C is a trivalent metal element such as In, Ga, Al, etc.) (Patent Document 3).
[0004] ε-Fe2O3 and ε-type iron oxides are not thermodynamically stable phases, and therefore, special methods are required for their production. In the above-mentioned patent documents 1 to 3, a method for producing ε-Fe2O3 or ε-type iron oxides is disclosed, in which fine crystals of oxyhydroxide or oxyhydroxide containing substitution elements generated by a liquid phase method are used as a precursor, silicon oxide is coated on the precursor by a sol-gel method, and then heat-treated. As liquid phase methods, a reverse micelle method using an organic solvent as a reaction medium and a method using only an aqueous solution as a reaction medium are disclosed, respectively.
[0005] In addition, the above-mentioned ε-Fe2O3 and ε-type iron-based oxides are shown in, for example, Patent Documents 4 to 5 to have a peak of radio wave absorption in a high frequency region exceeding 100 GHz, and are also expected to be used as radio wave absorbers.
[0006] However, the magnetic particle powder obtained by the production methods disclosed in Patent Documents 1 to 3 contains a considerable amount of non-magnetic α-type iron-based oxides as impurities in addition to ε-Fe2O3 and ε-type iron-based oxides.
[0007] Patent Document 6 discloses a technique for reducing the amount of α-type iron-based oxides as impurities contained in substituted ε-iron oxide magnetic particle powder.
[0008] Patent Document 7 discloses a method for producing an ε-type iron-based oxide by coating silicon oxide using a sol-gel method in a wide pH range.
[0009] Prior art literature
[0010] Patent Literature
[0011] Patent Document 1: Japanese Patent Application Publication No. 2008-174405
[0012] Patent Document 2: International Publication No. 2008 / 029861
[0013] Patent Document 3: International Publication No. 2008 / 149785
[0014] Patent Document 4: Japanese Patent Application Publication No. 2008-277726
[0015] Patent Document 5: Japanese Patent Application Publication No. 2009-224414
[0016] Patent Document 6: Japanese Patent Application Publication No. 2016-130208
[0017] Patent Document 7: Japanese Patent Application Publication No. 2018-092691 Summary of the invention
[0018] Problems to be solved by the invention
[0019] The ε-type iron-based oxide in which a part of the Fe sites are replaced by the production method disclosed in the above-mentioned Patent Document 4 has a reduced content of α-type iron-based oxide as an impurity compared to the ε-type iron-based oxide produced by the conventional method. However, the ε-type iron-based oxide is a metastable phase, and when the amount of Fe replaced by other metal elements is small, even if the production method disclosed in Patent Document 4 is used, it is difficult to obtain the same space group as ε-Fe2O3, and sometimes the reduction in the content of the α-type iron-based oxide is insufficient.
[0020] α-type iron oxides are non-magnetic, so when substitutional ε-iron oxide magnetic particle powder is used as a radio wave absorbing material, it does not contribute to the radio wave absorption properties, and when used in magnetic recording media, it does not contribute to improving the recording density. Therefore, its content needs to be reduced.
[0021] That is, the technical problem to be solved in the present invention is to provide a substitutional epsilon iron oxide magnetic particle powder having a reduced content of non-magnetic α-type iron-based oxides and a method for producing the substitutional epsilon iron oxide magnetic particle powder.
[0022] Means for solving problems
[0023] In order to obtain substituted ε iron oxide magnetic particle powder, the inventors conducted intensive research focusing on the need to heat the precursor of the magnetic particle powder in a state coated with silicon oxide, and found that the content of α-type iron-based oxides can be reduced by adding a silicon compound having a hydrolyzable group for coating to an aqueous solution containing the precursor at a pH of above 2.0 and below 7.0.
[0024] Based on the above findings, the present inventors have completed the present invention described below.
[0025] In order to solve the above-mentioned problems, the present invention provides a substitutional ε iron oxide magnetic particle powder, which is a substitutional ε iron oxide magnetic particle powder mainly comprising an ε-type iron-based oxide formed by replacing a part of the Fe sites of ε-Fe2O3 with other metal elements, wherein, when the number of moles of Fe contained in the above-mentioned substitutional ε iron oxide magnetic particle powder is set to Fe and the number of moles of all metal elements replacing the Fe sites is set to Me, the amount of Fe replaced by other metal elements defined by Me / (Fe+Me) is greater than 0.08 and less than 0.17, and the content of α-type iron-based oxide measured by X-ray diffraction method is less than 3%.
[0026] The other metal element replacing a part of the Fe site is preferably Co, Ti, and one or more selected from Ga and Al. For example, an ε-type iron-based oxide containing Co and Ti and one or more selected from Ga and Al as the other metal element replacing a part of the Fe site is a suitable target.
[0027] The present invention also provides a powder compact comprising the above-mentioned substitutional epsilon iron oxide magnetic particle powder.
[0028] The present invention also provides a radio wave absorber in which the above-mentioned substituted ε iron oxide magnetic particle powder is dispersed in a resin or rubber.
[0029] The present invention also provides a method for producing a substitutional ε iron oxide magnetic particle powder, which is a method for producing a substitutional ε iron oxide magnetic particle powder of an ε-type iron-based oxide mainly comprising replacing a portion of the Fe sites of ε-Fe2O3 with other metal elements, comprising: a neutralization step, using an acidic aqueous solution comprising trivalent iron ions and ions of a metal to be substituted for a portion of the above-mentioned Fe sites as a raw material solution, adding a base to the above-mentioned raw material solution to neutralize it to a pH range of not less than 8.0 and not more than 10.0, thereby obtaining a dispersion containing hydroxyl iron containing the substituted metal element, or a mixture of hydroxyl iron and a hydroxide of the substituted metal element; a silicon compound adding step, adding a silicon compound having a hydrolyzable group to the above-mentioned dispersion containing hydroxyl iron containing the above-mentioned substituted metal element, or a mixture of hydroxyl iron and a hydroxide of the substituted metal element; and an aging step, Or a mixture of ferric oxyhydroxide and a hydroxide of a substituting metal element and the dispersion of the silicon compound are maintained at a pH of 8.0 to 10.0, and the chemical reaction product of the silicon compound is coated on the ferric oxyhydroxide containing the substituting metal element, or the mixture of ferric oxyhydroxide and a hydroxide of a substituting metal element; wherein, in the neutralization step, the addition of the silicon compound having a hydrolyzable group is started at a time when the pH of the dispersion is in the range of 2.0 to 7.0, and when the number of moles of the silicon compound added to the dispersion at a pH of 2.0 to 7.0 is S1, the number of moles of Fe ions contained in the raw material solution is F, and the total number of moles of the substituting metal element ions is M, S1 / (F+M) is 0.01 to 10.0, and when the total number of moles of the silicon compound added is S2, S2 / (F+M) is 0.50 to 10.0.
[0030] In the above-mentioned manufacturing method, the addition of alkali in the above-mentioned neutralization step and the addition of silicon compound in the above-mentioned silicon compound addition step can be carried out continuously, the addition of alkali can be carried out continuously and the addition of silicon compound can be carried out intermittently, the addition of alkali and the addition of silicon compound can be carried out intermittently, or the addition of alkali can be carried out intermittently and the addition of silicon compound can be carried out continuously.
[0031] In addition, in the above-mentioned production method, the other metal element replacing a part of the above-mentioned Fe site is preferably Co, Ti, and one or more selected from Ga and Al. For example, as the other metal element replacing a part of the Fe site, it is preferred to contain Co and Ti and contain one or more selected from Ga and Al.
[0032] The present invention also provides a method for producing a green compact by compression-molding the above-mentioned substituted epsilon iron oxide magnetic particle powder to obtain a green compact.
[0033] Effects of the Invention
[0034] As described above, by using the production method of the present invention, it is possible to obtain substitutional ε iron oxide magnetic particle powder having a reduced content of α-type iron-based oxides, and a powder compact and a radio wave absorber using the same. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 This is a schematic diagram showing an example of an embodiment of the present invention.
[0036] Figure 2 This is a schematic diagram showing an example of an embodiment of the present invention.
[0037] Figure 3 This is a schematic diagram showing an example of an embodiment of the present invention.
[0038] Figure 4 This is a schematic diagram showing an example of an embodiment of the present invention.
[0039] Figure 5 This is a schematic diagram showing an example of an embodiment of the present invention.
[0040] Figure 6 This is a schematic diagram showing an example of an embodiment of the present invention. DETAILED DESCRIPTION
[0041] [Iron oxide magnetic particle powder]
[0042] The manufacturing method of the present invention is used to manufacture substitutional ε iron oxide magnetic particle powder mainly comprising ε-type iron oxide formed by replacing a part of the Fe sites of ε-Fe2O3 with other metal elements, and the magnetic particle powder is mixed with a heterogeneous phase that is an inevitable impurity in its manufacturing. The heterogeneous phase is mainly α-type iron oxide, and the iron oxide magnetic particle powder obtained by the present invention is essentially composed of ε-type iron oxide magnetic particles and α-type iron oxide. The purpose of the present invention is to reduce the content of α-type iron oxide as a heterogeneous phase.
[0043] Whether a part of the substitution body formed by replacing a part of the Fe sites of ε-Fe2O3 with other metal elements has an ε structure can be confirmed by using X-ray diffraction (XRD), high speed electron diffraction (HEED), etc. In the present invention, the identification of ε-type and α-type iron-based oxides is carried out by XRD.
[0044] The following examples are given as some of the replacement bodies that can be produced by the production method of the present invention.
[0045] By the general formula ε-C z Fe 2-z A substitution product represented by O3 (wherein C is one or more trivalent metal elements selected from In, Ga, and Al).
[0046] By the general formula ε-A x B y Fe 2-x-y A substitution product represented by O3 (wherein A is one or more divalent metal elements selected from Co, Ni, Mn, and Zn, and B is one or more tetravalent metal elements selected from Ti and Sn).
[0047] By the general formula ε-A x C z Fe 2-x-z A substitution product represented by O3 (wherein A is one or more divalent metal elements selected from Co, Ni, Mn, and Zn, and C is one or more trivalent metal elements selected from In, Ga, and Al).
[0048] By the general formula ε-B y C z Fe 2-y-z A substitution product represented by O3 (wherein B is one or more tetravalent metal elements selected from Ti and Sn, and C is one or more trivalent metal elements selected from In, Ga, and Al).
[0049] By the general formula ε-A x B y C z Fe 2-x-y-z A substitution body represented by O3 (wherein A is one or more divalent metal elements selected from Co, Ni, Mn, and Zn, B is one or more tetravalent metal elements selected from Ti and Sn, and C is one or more trivalent metal elements selected from In, Ga, and Al).
[0050] Here, the type in which only the C element is substituted has the advantage of being able to arbitrarily control the coercivity of the magnetic particles and being easy to obtain the same space group as ε-Fe2O3, but sometimes has poor thermal stability. In particular, when Ga and Al are used as C, the thermal stability of the obtained substitution type ε iron oxide magnetic particle powder is somewhat poor, so it is preferred to further substitute with A and / or B elements at the same time. The three-element substitution type of A, B and C best achieves the balance of the above-mentioned characteristics, and is excellent in heat resistance, availability of a single phase, and controllability of coercivity. When Ga and Al are used as C, it is preferred to substitute Co and Ti at the same time.
[0051] It should be noted that the production method of the present invention is applicable to any of the above-mentioned substitutional iron oxide magnetic particles.
[0052] The manufacturing method of the present invention described below can be applied even if the substitution amount of the metal element replacing the above-mentioned Fe site is any value, but it is effective to apply it with a substitution amount that easily generates α-type iron-based oxides. Specifically, when the molar number of Fe contained in the above-mentioned substitutional ε-iron oxide magnetic particle powder is set as Fe and the molar number of all metal elements replacing the Fe site is set as Me, when the substitution amount of Fe with other metal elements defined by Me / (Fe+Me) is 0.08 or more and 0.17 or less, it is possible to obtain a substitutional ε-iron oxide magnetic particle powder having an α-type iron-based oxide content of 3% or less measured by XRD, which cannot be obtained by conventional methods.
[0053] [Powder pressed body and radio wave absorber]
[0054] The substitutional ε iron oxide magnetic particle powder obtained by the present invention functions as a radio wave absorber having excellent radio wave absorption performance by forming a filling structure of the powder particles. The filling structure referred to here refers to a three-dimensional structure formed by each particle when the particles are in contact or close to each other. In order to provide for practical use of the radio wave absorber, it is necessary to maintain the filling structure. As a method for this, for example, a method of compression molding the substitutional ε iron oxide magnetic particle powder to form a pressed powder body, and a method of using a non-magnetic polymer compound as a binder to make the substitutional ε iron oxide magnetic particle powder adhere to form a filling structure can be cited.
[0055] In the case of the method using a binder, the substituted ε iron oxide magnetic particle powder is mixed with a non-magnetic polymer substrate to obtain a kneaded product. The amount of the radio wave absorbing material powder in the kneaded product is preferably set to 60% by mass or more. The more the amount of the radio wave absorbing material powder is mixed, the more advantageous it is in improving the radio wave absorption characteristics, but if it is too much, mixing with the polymer substrate becomes difficult, so it is necessary to pay attention. For example, the amount of the radio wave absorbing material powder can be set to 80-95% by mass or 85-95% by mass.
[0056] As the polymer substrate, various substrates that satisfy heat resistance, flame retardancy, durability, mechanical strength, and electrical properties can be used according to the use environment. For example, a suitable material can be selected from resins (nylon, etc.), gels (silicone, etc.), thermoplastic elastomers, rubber, etc. In addition, two or more polymer compounds can be blended to form the substrate.
[0057] [Average particle size]
[0058] In the present invention, the average particle size of the iron oxide magnetic particle powder obtained by the production method of the present invention is not particularly specified, but is preferably fine enough to form a single magnetic domain structure. Typically, the average particle size of the magnetic particle powder obtained by the transmission electron microscope is 10 nm or more and 40 nm or less.
[0059] [Starting materials and precursors]
[0060] In the manufacturing method of the present invention, as the starting material of the iron-based oxide magnetic particle powder, an acidic water-soluble solution containing trivalent iron ions and metal ions of the metal element that eventually replaces the Fe site (hereinafter referred to as the raw material solution) is used. If divalent Fe ions are used instead of trivalent Fe ions as the starting material, a mixture containing divalent iron hydroxide, magnetite, etc. in addition to trivalent iron hydroxide is generated as a precipitate, and the shape of the iron-based oxide particles finally obtained is deviated. Therefore, the substitutional ε iron oxide magnetic particle powder with a reduced content of α-type iron-based oxides as in the present invention cannot be obtained. Here, acidity means that the pH of the liquid is less than 7.0. As a supply source of these iron ions or metal ions of the replacement element, it is preferred to use water-soluble inorganic acid salts such as nitrates, sulfates, and chlorides in terms of ease of acquisition and price. When these metal salts are dissolved in water, the metal ions dissociate and the aqueous solution becomes acidic. When an alkali is added to the acidic aqueous solution containing the metal ions for neutralization, a mixture of iron oxyhydroxide and the hydroxide of the substitution element, or a precipitate of iron oxyhydroxide in which a part of the Fe site is substituted with another metal element (hereinafter collectively referred to as iron oxyhydroxide containing the substitution element) is obtained. In the production method of the present invention, iron oxyhydroxide containing these substitution elements is used as a precursor of the substitution-type ε iron oxide magnetic particle powder.
[0061] The total metal ion concentration in the raw material solution is not particularly specified in the present invention, but is preferably 0.01 mol / L or more and 0.5 mol / L or less. When it is less than 0.01 mol / L, the amount of substitutional ε iron oxide magnetic particle powder obtained by one reaction is small, which is not preferred in terms of economic efficiency. When the total metal ion concentration exceeds 0.5 mol / L, the reaction solution is easily gelled due to rapid precipitation of hydroxides, which is not preferred.
[0062] [Neutralization process]
[0063] In the manufacture method of the present invention, alkali is added to the raw material solution, and neutralized to a pH value of 8.0 or more and 10.0 or less, to obtain a dispersion of a precipitate of oxyhydroxide iron containing a replacement element. It should be noted that the hydroxide of trivalent iron ions mainly comprises oxyhydroxide. The pH of the dispersion is set to 8.0 or more here in order to complete the precipitation generation of the hydroxide of the replacement metal element (e.g., Co) and to promote the condensation reaction of the silanol derivative as a hydrolysis product. In the manufacture method of the present invention, the upper limit of the pH reached in the neutralization process is not particularly specified, and is preferably set to 10.0, because the effect of neutralization is saturated, and the effect of promoting the condensation reaction of the silanol derivative described later decreases.
[0064] The base used for neutralization can be any of alkali metal or alkaline earth metal hydroxides, ammonia water, ammonium bicarbonate and other ammonium salts, preferably ammonia water and ammonium bicarbonate, which are less likely to contain impurities when the ε-type iron oxide is finally obtained by heat treatment. These bases can be added to the aqueous solution of the starting material in the form of a solid, and are preferably added in the form of an aqueous solution from the viewpoint of ensuring the uniformity of the reaction.
[0065] As described above, when a base is added to the raw material solution for neutralization treatment, a precipitate of iron oxyhydroxide containing the substitution element is precipitated. Therefore, during the neutralization treatment, the dispersion containing the precipitate is stirred by a known mechanical means.
[0066] The addition of alkali to the raw material solution can be carried out continuously from the beginning of addition to the end. In addition, before the pH of the dispersion reaches 8.0, the addition of alkali can be interrupted and a prescribed pH holding time can be set. In this case, multiple pH holding times can be set and the addition of alkali can be carried out intermittently. It should be noted that the number of times the pH holding time is set, i.e., the number of times the addition of alkali is interrupted, is preferably set to less than 3 times to avoid the complication of the manufacturing process.
[0067] In the production method of the present invention, the reaction temperature during the neutralization treatment is set to be 5°C or more and 60°C or less. When the reaction temperature is less than 5°C, the cost due to cooling increases, so it is not preferred. When it exceeds 60°C, α-type oxides that are ultimately heterogeneous are easily generated, so it is not preferred. More preferably, it is 10°C or more and 40°C or less. In the case of the production method described in the above-mentioned Patent Document 4, the neutralization treatment needs to be performed at a temperature of 5°C or more and 25°C or less, and a refrigerator needs to be used during the reaction, but in the production method of the present invention, the neutralization treatment can also be performed at a reaction temperature above room temperature.
[0068] It should be noted that the pH value described in this specification is measured using a glass electrode based on JIS Z8802. It refers to the value measured by a pH meter calibrated using an appropriate buffer solution corresponding to the pH range to be measured as a pH standard solution. In addition, the pH described in this specification is a value obtained by directly reading the measured value displayed by the pH meter compensated by the temperature compensation electrode under the reaction temperature conditions.
[0069] [Silicon compound adding step]
[0070] In the manufacturing method of the present invention, the precursor of the substitutional ε iron oxide magnetic particle powder generated in the above step, that is, the iron oxyhydroxide containing the substitutional element, is difficult to be transformed into an ε-type iron-based oxide even if subjected to heat treatment in its original state. Therefore, before the heat treatment, the iron oxyhydroxide containing the substitutional element needs to be coated with a chemical reaction product obtained by hydrolysis and condensation of a silicon compound. It should be noted that the chemical reaction product of the silicon compound referred to here refers not only to silicon oxides of stoichiometric composition, but also to substances of non-stoichiometric composition such as silanol derivatives and polysiloxane structures described later, and substances that are transformed into silicon oxides by heat treatment.
[0071] In the production methods described in Patent Documents 1 to 4, a sol-gel method is used as a coating method for the chemical reaction product of the silicon compound, and a silicon compound having a hydrolyzable group is added to the reaction solution after the neutralization treatment of the raw material solution is completed and the pH of the reaction solution becomes alkaline. On the other hand, in the production method of the present invention, the same sol-gel method is used as a coating method for silicon oxide, but it is characterized in that the silicon compound having a hydrolyzable group is added at a time when the pH of the reaction solution is in the range of pH 2.0 or more and 7.0 or less, which is on the acidic side, before the neutralization of the raw material solution is completed. It should be noted that the end time of the addition of the silicon compound will be described later.
[0072] In the case of the sol-gel method, alkoxysilanes such as silicon compounds having hydrolyzable groups (e.g., tetraethoxysilane (TEOS), tetramethoxysilane (TMOS)) and silane compounds such as various silane coupling agents are added to a dispersion containing iron oxyhydroxide containing a substituting element, and a hydrolysis reaction is caused to occur under stirring, and the generated silanol derivatives are condensed to form polysiloxane bonds, thereby coating the surface of the iron oxyhydroxide containing the substituting element.
[0073] The present inventors have found that starting the addition of the silicon compound having a hydrolyzable group at a pH of 2.0 to 7.0 can reduce the content of α-type iron-based oxides in the finally obtained substituted ε-iron oxide magnetic particle powder. The reason for this is believed to be as follows.
[0074] The speed of the hydrolysis reaction of the silicon compound having a hydrolyzable group and the condensation reaction of the silanol derivative as the hydrolysis product varies depending on the pH of the reaction system. The hydrolysis reaction speed is generally high in the low pH region on the acidic side, decreases as the pH rises, and increases again in the high pH region on the alkaline side. The condensation reaction speed is low in the low pH region on the acidic side, increases as the pH rises, and becomes high in the pH region from the neutral to the alkaline side.
[0075] When a silicon compound having a hydrolyzable group is added to a dispersion containing a precipitate of iron oxyhydroxide containing a substitution element in a low pH region on the acidic side, the hydrolysis of the silicon compound proceeds rapidly to generate a silanol derivative having a small amount of organic components, while the condensation reaction of the generated silanol derivative does not proceed. Here, the silanol derivative has an OH group as a hydrophilic group and is uniformly distributed in the aqueous solution, so it is considered that a state is formed in which the precipitate of iron oxyhydroxide containing a substitution element and the silanol derivative are uniformly dispersed and coexist in the dispersion.
[0076] Thereafter, if the pH of the dispersion is further increased, the condensation reaction of the silanol derivative becomes dominant, so that the precipitate of the iron oxyhydroxide containing the substitution element is uniformly covered with the silanol derivative or its condensation reaction product. Therefore, it is considered that the content of the α-type iron-based oxide contained in the substituted ε-iron oxide magnetic particle powder obtained by the final heat treatment is reduced.
[0077] It should be noted that the above-mentioned Patent Document 5 discloses coating silicon oxide by a sol-gel method in a wide pH range, but in this case, the addition of the silicon compound is carried out at a certain pH after the neutralization treatment is completed, and there is no disclosure of a technical concept that takes into account both the hydrolysis reaction rate and the condensation reaction rate of the silicon compound as in the present invention.
[0078] The pH at the time of starting to add the silicon compound having a hydrolyzable group is preferably above 2.0. When the pH is less than 2.0, the precipitation formation of the hydroxide of the trivalent iron ion contained in the raw material solution, which is the main component of the substitution-type ε iron oxide magnetic particle powder, may become insufficient. The pH at the time of starting to add is more preferably above 3.0. In addition, the pH at the time of starting to add the silicon compound having a hydrolyzable group is preferably below 7.0. When the pH exceeds 7.0, the hydrolysis reaction slows down and the generation of the silanol derivative becomes insufficient. Therefore, the precipitation of the oxyhydroxide iron containing the substitution element and the silanol derivative are no longer uniformly distributed and coexist in the dispersion, and the precipitation of the oxyhydroxide iron containing the substitution element is difficult to be uniformly covered by the silanol derivative or its condensation reaction product. The pH at the time of starting to add is preferably below 6.0, and more preferably below 4.0.
[0079] The addition of the silicon compound having a hydrolyzable group begins at the time when the pH of the raw material solution reaches the desired value in the neutralization step. The addition of the silicon compound can be performed continuously from the start of the addition to the end. The so-called continuous here includes adding the entire amount of the silicon compound added to the dispersion to the dispersion at once. In addition, the addition of the silicon compound can be divided into several times and performed intermittently.
[0080] In the production method of the present invention, the amount of the silicon compound added to the dispersion liquid needs to satisfy the following two conditions simultaneously.
[0081] The first condition is the amount of silicon compound added to the dispersion with a pH of 2.0 or more and 7.0 or less. When the number of moles of the silicon compound added to the dispersion with a pH of 2.0 or more and 7.0 or less is S1, the number of moles of Fe ions contained in the raw material solution is F, and the total number of moles of the substituted metal element ions is M, S1 / (F+M) is set to be greater than 0.01 and less than 10.0. When S1 / (F+M) is less than 0.01, the amount of silanol derivatives coexisting with the precipitate of oxyhydroxide containing the substituted element is small, and the effect of uniformly coating the precipitate of oxyhydroxide containing the substituted element with silanol derivatives or their condensation reaction products is reduced, so it is not preferred. When the amount of silicon compound added is increased, the processing volume of the heating process and the silicon oxide removal process described later increases, and the manufacturing cost increases, so S1 / (F+M) is preferably less than 10.0.
[0082] The second condition is the amount of silicon compound added in the entire manufacturing process. When the total number of moles of silicon compound added is set to S2, the number of moles of Fe ions contained in the raw material solution is set to F, and the total number of moles of ions of the replacing metal element is set to M, S2 / (F+M) is set to be greater than 0.50 and less than 10.0. When S2 is less than 0.50, the amount of coating of the chemical reaction product of the silicon compound coated on the surface of the precipitate of oxyhydroxide containing the replacing element becomes less, and as a result, there is a disadvantage that α-type iron-based oxides are easily generated, which is not preferred. In addition, when S2 / (F+M) exceeds 10.0, the processing volume of the heating process and the silicon oxide removal process described later increases, and the manufacturing cost increases, so it is not preferred.
[0083] In addition, when the entire amount of the silicon compound is added within the range of pH 2.0 to 7.0, S1=S2.
[0084] [Embodiments of the present invention]
[0085] As described above, in the production method of the present invention, the addition of the alkali in the neutralization step and the addition of the silicon compound in the silicon compound addition step can be performed continuously or intermittently. Therefore, in the production method of the present invention, various embodiments can be adopted by combining the addition of the alkali and the addition of the silicon compound. Some embodiments of the present invention are illustrated below, but the production method of the present invention is not limited to the embodiments described below.
[0086] Figure 1 The time elapsed in an embodiment of continuously performing both the addition of alkali and the addition of silicon compound is schematically illustrated. In this case, after the addition of alkali is started, the addition of silicon compound is started at the moment when the pH of the raw material solution reaches a specified pH in the range of not less than 2.0 and not more than 7.0. In the case of this embodiment, the neutralization step and the silicon compound addition step are not temporally continuous steps, but parallel steps. As shown in this figure, the addition of silicon compound can be continued after the addition of alkali is completed, can be completed at the moment when the addition of alkali is completed, or can be completed at the moment when the pH is below 7.0. In the case where the addition of silicon compound is still carried out after the addition of alkali is completed, considering the time of the entire manufacturing process, it is preferred to complete the addition of silicon compound within 120 minutes after the addition of alkali is completed. After the addition of silicon compound is completed, a aging step described later is provided.
[0087] Although not specifically shown in the figure, Figure 1 In the embodiment, the silicon compound may be added in multiple times and performed intermittently.
[0088] Figure 2 Schematically illustrates the time elapse of an embodiment in which the addition of alkali is interrupted in the middle of the neutralization step. In this case, the addition of alkali is interrupted once, and the entire amount of the silicon compound is added continuously during the pH holding time during which the addition of alkali is interrupted, and S1=S2.
[0089] Figure 3 Schematically illustrates another example of the time elapse of the interruption of the addition of the alkali. In this case, the addition of the silicon compound starts when the pH of the raw material solution reaches a predetermined pH in the range of 2.0 to 7.0, but the addition ends after the neutralization step is completed, and the addition of the silicon compound is continuous.
[0090] Figure 4 and Figure 5 The time elapse of an example of an embodiment in which the addition of the base is interrupted once and the addition of the silicon compound is performed intermittently is schematically illustrated in FIG. Figure 4 The addition of the silicon compound is carried out twice. Figure 5 It is divided into three times.
[0091] Figure 6 Schematically illustrates the time elapse of an example of an embodiment in which the secondary addition of the alkali is interrupted and the tertiary addition of the silicon compound is intermittently performed.
[0092] It should be noted that, as described above, the manufacturing method of the present invention is not limited to Figure 1 to Figure 6 In the embodiment illustrated in the above, the addition of the base in the neutralization step and the addition of the silicon compound in the silicon compound adding step can be arbitrarily combined.
[0093] [Ripening process]
[0094] Even if the pH is set to 8.0 or above, the condensation reaction of the silanol derivatives still proceeds slowly. Therefore, the dispersion liquid containing the chemical reaction product of the oxyhydroxide containing the substitution element and the silicon compound obtained by the neutralization step and the silicon compound addition step is maintained at a pH of 8.0 or above and matured to carry out the condensation reaction of the silanol derivatives. As a result, a uniform coating layer of the condensation reaction product of the silanol derivative is formed on the surface of the precipitate of the oxyhydroxide containing the substitution element. It is believed that the coating layer covers almost the entire surface of the precipitate of the oxyhydroxide containing the substitution element, but within the range that the effect of the present invention can be achieved, the uncoated part of the precipitate surface of the oxyhydroxide containing the substitution element is allowed. The above-mentioned aging time is preferably 1 hour or more and 24 hours or less. When the holding time is less than 1 hour, the coating of the precipitate of the oxyhydroxide containing the substitution element caused by the condensation of the silanol derivative is not completed, and α-type iron-based oxides are easily generated. When it exceeds 24 hours, the aging effect is saturated, so it is not preferred. The aging time is the time after the completion of addition of the silicon compound when the addition of the silicon compound continues after the completion of the neutralization step, and is the time after the completion of addition of the alkali when the addition of the silicon compound is completed before the completion of the neutralization step.
[0095] In the method for producing substituted epsilon iron oxide magnetic particle powder of the present invention, the steps after the aging step can be the same as those in the conventional production methods described in, for example, Patent Documents 1 to 4. Specifically, the following steps can be mentioned.
[0096] [Heating process]
[0097] In the manufacturing method of the present invention, after the iron hydroxide oxide containing the substitution element coated with the condensation reaction product of the above-mentioned silanol derivative is recovered by a known solid-liquid separation method, a heat treatment is performed to obtain an ε-type iron-based oxide. Before the heat treatment, a cleaning and drying process may be provided. The heat treatment is carried out in an oxidizing atmosphere, and the oxidizing atmosphere may be an atmospheric atmosphere. The heating may be carried out in a range of about 700°C to 1300°C. When the heating temperature is high, α-Fe2O3 (which is an impurity relative to ε-Fe2O3) belonging to a thermodynamically stable phase is easily generated. Therefore, the heat treatment is preferably carried out at a temperature of 900°C to 1200°C, and more preferably at a temperature of 950°C to 1150°C.
[0098] The heat treatment time can be adjusted in the range of about 0.5H to 10H, and good results are easily obtained in the range of 2H to 5H. It is believed that the presence of the silicon-containing material covering the particles plays an advantageous role in causing a phase transition to an ε-type iron-based oxide instead of an α-type iron-based oxide. In addition, the silicon oxide coating has the effect of preventing the iron oxyhydroxide crystals containing the substitution element from sintering each other during the heat treatment.
[0099] When the ε-type iron-based oxide magnetic particle powder does not need to be coated with silicon oxide, the silicon oxide coating may be removed after the heat treatment.
[0100] [Composition analysis using high-frequency inductively coupled plasma emission spectrometry (ICP)]
[0101] The composition of the obtained substituted ε iron oxide magnetic particle powder was analyzed by dissolution method. The composition analysis was performed using ICP-720ES manufactured by Agilent Technologies, with measurement wavelengths (nm) of Fe: 259.940 nm, Ga: 294.363 nm, Co: 230.786 nm, Ti: 336.122 nm, and Si: 288.158 nm.
[0102] [Measurement of hysteresis curve (bulk BH curve)]
[0103] A vibrating sample magnetometer VSM (VSM-P7 manufactured by Toei Industry Co., Ltd.) was used with an applied magnetic field of 1193 kA / m (15 kOe) and a measurement range of M of 0.005 A·m 2 The magnetic properties were measured with a stepping bit of 140 bits, a time constant of 0.03 seconds, and a waiting time of 0.1 seconds. The coercive force Hc and saturation magnetization σs were evaluated based on the BH curve.
[0104] [Evaluation of crystallinity by X-ray diffraction (XRD)]
[0105] The obtained sample was subjected to powder X-ray diffraction (XRD: sample horizontal multi-purpose X-ray diffractometer Ultima IV manufactured by Rigaku Corporation, ray source CuKα ray, voltage 40 kV, current 40 mA, 2θ=10° or more and 70° or less). The obtained diffraction pattern was evaluated by Rietveld analysis based on ICSD (Inorganic Crystal Structure Database) No. 173025: Iron (III) Oxide-Epsilon, No. 82134: Hematite, using integrated powder X-ray analysis software (PDXL2: manufactured by Rigaku Corporation), and the crystal structure and the content of the α phase were confirmed.
[0106] [BET specific surface area]
[0107] The BET specific surface area was determined by the BET single-point method using Macsorb model-1210 manufactured by Macsorb Corporation.
[0108] TEM observation of the substitutional ε iron oxide magnetic particle powder obtained by the production method of the present invention was performed under the following conditions. JEM-1011 manufactured by JEOL Ltd. was used for TEM observation. TEM photographs taken at magnifications of 10,000 and 100,000 were used for particle observation (the product after the silicon oxide coating was removed).
[0109] -Measurement of average particle size and particle size distribution evaluation (coefficient of variation (%))-
[0110] The TEM average particle size and particle size distribution evaluation (coefficient of variation (%) were digitized. Mac-View Ver.4.0 was used as image processing software. When using this image software, the particle size of a certain particle was calculated as the length of the long side of the rectangle with the smallest area among the rectangles circumscribed with the particle. As for the number of particles, more than 200 particles were measured.
[0111] The selection criteria of the particles to be measured among the particles reflected in the transmission electron micrograph are as follows.
[0112] [1] Particles whose parts are outside the field of view of the photograph are not measured.
[0113] [2] Measurement of isolated particles with clear outlines.
[0114] [3] Particles can be measured independently and as individual particles, even when the particle shape deviates from the average.
[0115] [4] For particles that overlap but have clear boundaries and can be judged as a whole, each particle is measured as a single particle.
[0116] [5] Overlapping particles whose boundaries are unclear and whose overall shapes cannot be determined are not measured as particles whose shapes cannot be determined.
[0117] The number average value of the particle diameters of the particles selected according to the above criteria was calculated as the average particle diameter of the substituted ε iron oxide magnetic particle powder observed by TEM.
[0118] [Measurement of radio wave absorption characteristics]
[0119] 1.2 g of substitutional ε iron oxide powder was pressed at 28 MPa (20 kN) to obtain a powder compact with a diameter of 13 mm and a thickness of 3 mm. The transmission attenuation of the obtained powder compact was measured using terahertz time-domain spectroscopy. Specifically, the terahertz spectrometer TAS7400SL manufactured by Advantest Co., Ltd. was used to measure the powder compact when it was placed in a sample holder and when a blank sample was used. The measurement conditions were as follows.
[0120] Sample holder diameter:
[0121] ·Measurement mode: transmission
[0122] Frequency resolution: 1.9GHz
[0123] Vertical axis: absorbance
[0124] ·Horizontal axis: frequency [THz]
[0125] Cumulative number (samples): 2048
[0126] Cumulative number (blank sample): 2048
[0127] The observed signal waveform of the sample and the reference waveform of the blank sample were expanded to 2112 ps and Fourier transformed, and the ratio (Ssig / Sref) of the obtained Fourier spectra (respectively set as Sref and Ssig) was obtained to calculate the transmission attenuation of the powder compact placed on the sample holder.
[0128] Example
[0129] [Example 1]
[0130] In a 5L reaction tank, 283.26g of 99% pure iron nitrate nonahydrate (III), 56.36g of 11.55mass% Ga nitrate (III) solution, 6.25g of 97% pure cobalt nitrate (II) hexahydrate, and 6.61g of 15.1mass% Ti concentration were dissolved in 3813.21g pure water while mechanically stirring with a stirring blade to obtain a raw material solution (step 1). The pH of the raw material solution is about 1. The molar ratio of the metal ions in the raw material solution is Fe:Ga:Co:Ti=1.677:0.223:0.050:0.050. It should be noted that the Roman numerals in parentheses after the reagent name represent the valence of the metal element.
[0131] To this raw material solution, 294.85 g of a 22.30 mass % ammonia aqueous solution was added over 90 minutes under an air atmosphere at 20° C. while mechanically stirring with a stirring blade (Step 2).
[0132] After 60 minutes, when the pH of the reaction solution after adding the ammonia solution reached 4.0, 519.22 g of tetraethoxysilane (TEOS) with a purity of 95.0 mass% was added in parallel as a silicon compound having a hydrolyzable group, and the addition lasted for 30 minutes. After all the ammonia solution was added, stirring was continued for 20 hours in this state, and the precipitate of iron oxyhydroxide containing the substitution element was coated with the chemical reaction product of the silicon compound (step 3). The pH of the reaction solution at the end of the addition of the ammonia solution and the pH of the reaction solution during the above 20 hours of stirring were both 8.8. It should be noted that under this condition, the molar ratio S1 / (F+M) of the amount of Si element contained in tetraethoxysilane added to the dispersion having a pH of greater than 2.0 and less than 7.0 to the amount of iron, gallium, cobalt, and titanium ions contained in the raw material solution is 0.34, and the molar ratio S2 / (F+M) of the total amount of Si element contained in tetraethoxysilane added dropwise to the dispersion to the amount of iron, gallium, cobalt, and titanium ions contained in the raw material solution is 2.84.
[0133] The slurry obtained in step 3 is filtered, and the water content of the precipitate of iron oxyhydroxide containing the substitution element coated with the chemical reaction product of the silicon compound is removed as much as possible, and then it is dispersed in pure water again and washed by bubbling. The washed slurry is filtered again, and the obtained filter cake is dried in the air at 110°C (step 4).
[0134] The dried product obtained in step 4 was heated in air at 1090°C for 4 hours using a box-type calcining furnace to obtain iron-based oxide magnetic powder coated with silicon oxide (step 5). The chemical reaction product of the silicon compound dehydrates and changes into oxide when heat-treated in air.
[0135] The production conditions such as the charging conditions of the raw material solution of this example are shown in Table 1. Table 1 also shows the production conditions of other examples and comparative examples.
[0136] The heat-treated powder obtained by heat-treating the precipitate of oxyhydroxide containing the substitution element covered by the chemical reaction product of the silicon compound obtained in step 5 was stirred at about 60°C for 24 hours in a 17.58 mass% NaOH aqueous solution to remove the silicon oxide coating on the particle surface (step 6). Next, the slurry was washed with a centrifugal separator until the conductivity became 500mS / m or less, filtered with a membrane filter and dried, and the obtained iron-based oxide magnetic powder was subjected to chemical analysis of the composition, XRD measurement, and magnetic property measurement. These measurement results are shown in Table 2. Table 2 also shows the physical property values of the substitutional ε iron oxide magnetic particle powder obtained in other examples and comparative examples.
[0137] The substituted ε iron oxide magnetic particle powder involved in Example 1 was subjected to XRD measurement, and the content of the α phase was found to be 1.3%. This value is better than the value of the substituted ε iron oxide powder obtained by providing an intermediate aging step after the pH is adjusted to 8.9 after the ammonia solution is added, and then TEOS is added at pH 8.9 in Comparative Example 1 described later. In addition, chemical analysis of the composition and evaluation of magnetic properties were performed. The measurement results are shown in Table 2.
[0138] [Example 2]
[0139] As Example 2, a substitutional ε iron oxide magnetic particle powder was obtained by the same procedure as Example 1 except that the temperature at the time of adding the ammonia solution was set to 30°C, the time of adding the ammonia solution was set to 30 minutes, the pH at the start of TEOS addition was set to 6.0, and the rate of TEOS addition was set to 5.88 g / min during the addition of the ammonia solution and 22.47 g / min after the addition of the ammonia solution was completed. The pH at the time of the completion of the addition of the ammonia solution was 8.9, and the pH of the reaction solution at the time of the completion of the addition of TEOS and the pH of the reaction solution during the above-mentioned 20-hour stirring were both 8.8. The substitutional ε iron oxide magnetic particle powder involved in Example 2 was measured by XRD, and the content of the α phase was found to be 3.0%. This value is better than the value of the substitutional ε iron oxide magnetic particle powder obtained by the aging step of 30 minutes after the pH was 8.9 after the addition of the ammonia solution, and then TEOS was added at a pH of 8.9. In addition, chemical analysis of the composition and evaluation of magnetic properties were performed. The measurement results are shown in Table 2.
[0140] [Comparative Example 1]
[0141] As Comparative Example 1, a substitutional ε iron oxide magnetic particle powder was obtained by the same steps as in Example 1 except that TEOS was added at the time when the ammonia solution was added and the pH became 8.9, and an aging step was provided thereafter. It should be noted that the pH at the time of completion of ammonia addition was 8.9, and the pH of the reaction solution at the time of completion of TEOS addition and the pH of the reaction solution during the above-mentioned 20 hours of stirring were both 8.8. The substitutional ε iron oxide magnetic particle powder involved in this Comparative Example 1 was measured by XRD, and the content of the α phase was found to be 3.6%, which is a value higher than that of Examples 1 to 6. In addition, chemical analysis of the composition and evaluation of magnetic properties were performed. The measurement results are shown in Table 2.
[0142] [Comparative Example 2]
[0143] As Comparative Example 2, the temperature at the time of adding the aqueous ammonia solution was set to 25°C, the time of adding the aqueous ammonia solution was set to 60 minutes, the intermediate aging step was set to 30 minutes after the pH of the dispersion reached 8.9 after the aqueous ammonia solution was added, and TEOS was then added at a pH of 8.9. The substitutional ε iron oxide magnetic particle powder was obtained by the same steps as in Example 1. It should be noted that the pH of the reaction solution at the time of the completion of the addition of TEOS and the pH of the reaction solution during the above-mentioned 20 hours of stirring were both 8.8. The substitutional ε iron oxide magnetic particle powder involved in this Comparative Example 2 was measured by XRD, and the content of the α phase was found to be 7.4%, which is a value higher than that of Examples 1 to 6. In addition, chemical analysis of the composition and evaluation of magnetic properties were performed. The measurement results are shown in Table 2.
[0144] [Comparative Example 3]
[0145] As Comparative Example 3, a substituted ε iron oxide magnetic particle powder was obtained by the same steps as in Example 2 except that an aging step was provided after adding an ammonia solution and the pH became 8.9, and then TEOS was added at a pH of 8.9. It should be noted that the pH of the reaction solution at the end of the addition of TEOS and the pH of the reaction solution during the above-mentioned 20 hours of stirring were both 8.8. The substituted ε iron oxide magnetic particle powder involved in this Comparative Example 3 was measured by XRD, and the content of the α phase was found to be 5.4%, which is a value higher than that of Examples 1 to 6. In addition, chemical analysis of the composition and evaluation of magnetic properties were performed. The measurement results are shown in Table 2.
[0146] According to the above results, when the neutralization treatment is continuously performed, the effect of setting the start time of TEOS addition to pH 2.0 or higher and pH 7.0 or lower is significant. In addition, as shown in the results of Example 2, in the case of the production method of the present invention, even if the neutralization treatment is performed at a temperature 30°C higher than room temperature, a substitutional ε iron oxide magnetic particle powder with a low α phase content is obtained.
[0147] [Example 3]
[0148] As Example 3, after adding the ammonia solution to pH 4.0 (first neutralization step), the addition of the ammonia solution was stopped, the addition of TEOS was started without an intermediate aging step, and the remaining ammonia solution was added after the addition of TEOS was completed (second neutralization step), and a substitutional ε iron oxide magnetic particle powder was obtained by the same procedure as in Example 1. It should be noted that the pH of the reaction solution at the end of the second neutralization step and the pH of the reaction solution after the above-mentioned 20-hour stirring were both 8.8. The substitutional ε iron oxide magnetic particle powder involved in Example 3 was measured by XRD, and the content of the α phase was found to be 0%. This value is better than those obtained by the substitutional ε iron oxide magnetic particle powders obtained by Comparative Examples 4 and 5 described later, in which the addition of the ammonia solution was stopped after the addition of the ammonia solution to pH 4.0 or 6.0 (first neutralization step), an intermediate aging step of 30 minutes was set, and then the addition of TEOS was started, but the second neutralization step was not set after the addition of TEOS was completed. In addition, chemical analysis of the composition and evaluation of magnetic properties were performed. The measurement results are shown in Table 2.
[0149] [Example 4]
[0150] In a 1L reaction tank, 104.81g of an iron (III) sulfate solution with an Fe concentration of 11.65 mass%, 14.32g of a Ga (III) nitrate solution with a Ga concentration of 11.55 mass%, 1.91g of cobalt (II) nitrate hexahydrate with a purity of 97%, and 2.02g of titanium (IV) sulfate with a Ti concentration of 15.1 mass% were dissolved in 737.71g of pure water in an air atmosphere while being mechanically stirred with a stirring blade (step 1). The pH of the solution was about 1. The molar ratio of the metal ions in the charge solution was Fe:Ga:Co:Ti=1.714:0.186:0.050:0.050.
[0151] In the air atmosphere, the charge solution was mechanically stirred with a stirring blade at 30°C and 15.00 g of a 22.30 mass% ammonia solution was added over 1.9 minutes (first neutralization step). After the dropwise addition was completed, stirring was continued for 30 minutes to mature the generated precipitate (intermediate aging step). At this time, the pH of the slurry containing the precipitate was 2.0 (step 2).
[0152] The slurry obtained in step 2 is stirred while adding 158.88 g of tetraethoxysilane (TEOS) with a purity of 95.0 mass% in air at 30°C for 10 minutes. After the addition of TEOS, 62.77 g of 22.30 mass% ammonia solution is added in 8.1 minutes (second neutralization step). The pH after the second neutralization step is 8.8. Thereafter, stirring is continued for 20 hours in this state, and the precipitate is coated with the chemical reaction product of the silicon compound (step 3). The pH of the reaction solution during the above 20 hours of stirring is 8.8. It should be noted that under this condition, the molar ratio S1 / (F+M) of the amount of Si element contained in tetraethoxysilane added to the dispersion having a pH of greater than 2.0 and less than 7.0 to the amount of iron, gallium, cobalt, and titanium ions contained in the raw material solution is 2.84, and the molar ratio S2 / (F+M) of the total amount of Si element contained in tetraethoxysilane added dropwise to the dispersion to the amount of iron, gallium, cobalt, and titanium ions contained in the raw material solution is also 2.84.
[0153] Thereafter, substitutional ε iron oxide magnetic particle powder was obtained by the same procedure as in Example 1. The substitutional ε iron oxide powder of Example 4 was subjected to XRD measurement, and the content of the α phase was found to be 0%. This value was better than those of the substitutional ε iron oxide magnetic particle powders obtained by Comparative Examples 4 and 5 described later. In addition, chemical analysis of the composition and evaluation of magnetic properties were performed. The measurement results are shown in Table 2.
[0154] [Example 5]
[0155] As Example 5, the amount of ammonia solution used in the first neutralization step and the addition time were set to 51.00 g and 6.5 min, the pH after the first neutralization step was set to 3.0, and the amount of ammonia solution used in the second neutralization step and the condition time were set to 27.24 g and 3.5 min. The same steps as in Example 4 were used to obtain a substitutional ε iron oxide magnetic particle powder. It should be noted that the pH of the reaction solution at the end of the second neutralization step and the pH of the reaction solution during the above-mentioned 20h stirring were both 8.8. The substitutional ε iron oxide magnetic particle powder involved in Example 5 was measured by XRD, and the content of the α phase was found to be 0%. This value is better than those of the substitutional ε iron oxide magnetic particles obtained by Comparative Examples 4 and 5 described later. In addition, chemical analysis of the composition and evaluation of magnetic properties were performed. The measurement results are shown in Table 2.
[0156] [Example 6]
[0157] As Example 6, the amount of ammonia solution used in the first neutralization step and the addition time were set to 53.00 g and 6.8 min, the pH after the first neutralization step was set to 4.0, and the amount of ammonia solution used in the second neutralization step and the condition time were set to 24.78 g and 3.2 min. The same steps as in Example 4 were used to obtain a substitutional ε iron oxide magnetic particle powder. It should be noted that the pH of the reaction solution after the second neutralization step and the pH of the reaction solution during the above-mentioned 20h stirring were 8.8. The substitutional ε iron oxide powder involved in Example 6 was measured by XRD, and the content of the α phase was found to be 0%. This value is better than those values of the substitutional ε iron oxide magnetic particle powder obtained by Comparative Examples 4 and 5 described later. In addition, chemical analysis of the composition and evaluation of magnetic properties were performed. The measurement results are shown in Table 1.
[0158] [Example 7]
[0159] In a 1L reaction tank, 102.73g of an iron (III) sulfate solution with an Fe concentration of 11.65 mass%, 10.74g of aluminum (III) nitrate 9 hydrate with a purity of 98%, 1.91g of cobalt (II) nitrate 6 hydrate with a purity of 97%, and 2.02g of titanium (IV) sulfate with a Ti concentration of 15.1 mass% were dissolved in 746.26g of pure water in an air atmosphere while being mechanically stirred with a stirring blade (step 1). The pH of the solution was about 1. The molar ratio of the metal ions in the charge solution was Fe:Al:Co:Ti=1.680:0.220:0.050:0.050.
[0160] In the air atmosphere, the charge solution was mechanically stirred with a stirring blade at 30°C and 51.59 g of a 22.30 mass% ammonia solution was added over 60 minutes (first neutralization step). After the dropwise addition was completed, stirring was continued for 10 minutes to mature the generated precipitate (intermediate aging step). At this time, the pH of the slurry containing the precipitate was 3.0 (step 2).
[0161] The slurry obtained in step 2 is stirred while 158.88 g of tetraethoxysilane (TEOS) with a purity of 95.0 mass% is added dropwise in the air at 30°C for 5 minutes. After the addition of TEOS is completed, 27.09 g of 22.30 mass% ammonia solution is added 14 minutes later (second neutralization step). The pH after the second neutralization step is 8.8. Thereafter, stirring is continued for 20 hours in this state, and the precipitate is coated with the chemical reaction product of the silicon compound (step 3). The pH of the reaction solution during the above 20 hours of stirring is 8.8. It should be noted that under this condition, the molar ratio S1 / (F+M) of the amount of Si element contained in tetraethoxysilane added to the dispersion having a pH of greater than 2.0 and less than 7.0 to the amount of iron, aluminum, cobalt, and titanium ions contained in the raw material solution is 2.84, and the molar ratio S2 / (F+M) of the total amount of Si element contained in tetraethoxysilane added dropwise to the dispersion to the amount of iron, aluminum, cobalt, and titanium ions contained in the raw material solution is 2.84.
[0162] Thereafter, substitutional ε iron oxide magnetic particle powder was obtained by the same procedure as in Example 1. The substitutional ε iron oxide powder of Example 7 was subjected to XRD measurement, and the content of the α phase was found to be 0%. This value is better than those of the substitutional ε iron oxide magnetic particle powders obtained by Comparative Examples 4 and 5 described later. In addition, chemical analysis of the composition and evaluation of magnetic properties were performed. The measurement results are shown in Table 2.
[0163] The radio wave absorption characteristics of the obtained substitutional ε iron oxide magnetic particle powder were measured by the above method. The results showed that the maximum absorption frequency of the powder compact in the frequency range of 50 GHz to 100 GHz was 80.1 GHz, and the transmission attenuation per unit thickness was 4.1 dB / mm.
[0164] [Comparative Example 4]
[0165] As Comparative Example 4, a substitutional ε iron oxide powder was obtained by the same steps as in Example 6 except that the second neutralization step was not performed. It should be noted that the pH of the reaction solution at the end of the addition of TEOS and the pH of the reaction solution during the above-mentioned 20 hours of stirring were 4.0. The substitutional ε iron oxide magnetic particle powder involved in this Comparative Example 4 was measured by XRD, and the content of the α phase was found to be 87.5%, which is a value higher than that of Examples 1 to 7. In addition, chemical analysis of the composition and evaluation of magnetic properties were performed. The measurement results are shown in Table 2.
[0166] [Comparative Example 5]
[0167] As Comparative Example 5, a substitutional ε iron oxide magnetic particle powder was obtained by the same procedure as Comparative Example 4 except that the amount of ammonia solution used in the first neutralization step and the addition time were set to 57.00 g and 7.3 min, and the pH at the end of the first neutralization step was set to 6.0. It should be noted that the pH of the reaction solution at the end of the addition of TEOS and the pH of the reaction solution during the above-mentioned 20 hours of stirring were 6.0. The substitutional ε iron oxide magnetic particle powder involved in this Comparative Example 5 was measured by XRD, and the content of the α phase was found to be 36.9%, which is a value higher than that of Examples 1 to 7. In addition, chemical analysis of the composition and evaluation of magnetic properties were performed. The measurement results are shown in Table 2.
[0168] The above results show that when the second neutralization step is not provided, substitutional ε iron oxide magnetic particle powder with a low α phase content cannot be obtained. In addition, almost the same results were obtained when either nitrate or sulfate was used as the iron raw material as the starting material.
[0169] [Example 8]
[0170] Substituted ε iron oxide magnetic particle powder was obtained by the same procedure as in Example 5 except that the stirring time in the intermediate aging step was set to 10 minutes and tetraethoxysilane (TEOS) was added over 5 minutes. The pH of the reaction solution at the end of the addition of TEOS was 3.0, and the pH of the reaction solution during the above 20 hours of stirring was 8.6.
[0171] The α-phase content of the obtained substitutional ε iron oxide magnetic particle powder was 0%, and the radio wave absorption characteristics were measured by the above method. As a result, the maximum absorption frequency of the powder compact in the frequency range of 50 GHz to 100 GHz was 67.2 GHz, and the transmission attenuation per unit thickness was 4.6 dB / mm.
[0172] [Comparative Example 6]
[0173] In a 5L reaction tank, 527.22g of an iron (III) sulfate solution with an Fe concentration of 11.58 mass%, 71.61g of a Ga (III) nitrate solution with a Ga concentration of 11.55 mass%, 9.57g of cobalt (II) nitrate hexahydrate with a purity of 97%, and 10.11g of titanium (IV) sulfate with a Ti concentration of 15.1 mass% were dissolved in 3688.56g of pure water in an air atmosphere while being mechanically stirred with a stirring blade (step 1). The pH of the solution was about 1. The molar ratio of the metal ions in the charge solution was Fe:Ga:Co:Ti=1.714:0.186:0.050:0.050.
[0174] In the air atmosphere, the charge solution was mechanically stirred with a stirring blade at 30°C and 388.91 g of a 22.30 mass% ammonia solution was added over 10 minutes (first neutralization step). After the dropwise addition was completed, stirring was continued for 30 minutes to mature the generated precipitate (intermediate aging step). At this time, the pH of the slurry containing the precipitate was 8.6 (step 2).
[0175] The slurry obtained in step 2 is stirred while 794.40 g of tetraethoxysilane (TEOS) with a purity of 95.0 mass% is added dropwise in the air at 30°C for 10 minutes. Stirring is then continued for 20 hours in this state to coat the precipitate with the chemical reaction product of the silicon compound (step 3). The pH of the reaction solution during the above 20 hours of stirring is 8.6. It should be noted that under this condition, the molar ratio S1 / (F+M) of the amount of Si element contained in tetraethoxysilane added to the dispersion having a pH of more than 2.0 and less than 7.0 to the amount of iron, gallium, cobalt, and titanium ions contained in the raw material solution is 0, and the molar ratio S2 / (F+M) of the total amount of Si element contained in tetraethoxysilane added to the dispersion to the amount of iron, gallium, cobalt, and titanium ions contained in the raw material solution is 2.84.
[0176] Thereafter, substitutional ε iron oxide magnetic particle powder was obtained by the same procedure as in Example 1. XRD measurement was performed on the substitutional ε iron oxide powder of Comparative Example 6 to determine the content of the α phase, which was 4.9%, a value higher than that of Example 8. In addition, chemical analysis of the composition, and evaluation of magnetic properties and radio wave absorption properties were performed. The measurement results are shown in Table 2.
[0177] [Example 9]
[0178] Substitution-type ε iron oxide powder was obtained by the same procedure as in Example 7 except that 101.50 g of iron (III) nitrate solution and 11.7 g of aluminum (III) nitrate 9 hydrate were used. It should be noted that the pH of the reaction solution at the end of the addition of TEOS was 3.0, and the pH of the reaction solution during the above-mentioned 20 h stirring was 8.6. The molar ratio of metal ions in the charge solution was Fe:Al:Co:Ti=1.660:0.240:0.050:0.050. Chemical analysis of the composition, evaluation of magnetic properties and radio wave absorption properties were performed. The measurement results are shown in Table 2.
[0179] [Comparative Example 7]
[0180] In a 1L reaction tank, 101.51g of an iron (III) sulfate solution with an Fe concentration of 11.65 mass%, 11.72g of Al (III) nitrate 9 hydrate with a purity of 98%, 1.91g of cobalt (II) nitrate 6 hydrate with a purity of 97%, and 2.12g of titanium (IV) sulfate with a Ti concentration of 15.1 mass% were dissolved in 746.36g of pure water in an air atmosphere while being mechanically stirred with a stirring blade (step 1). The pH of the solution was about 1. The molar ratio of the metal ions in the charge solution was Fe:Al:Co:Ti=1.660:0.240:0.050:0.050.
[0181] In the air atmosphere, the charge solution was mechanically stirred with a stirring blade at 30°C and 78.68 g of a 22.30 mass% ammonia solution was added over 10 minutes (first neutralization step). After the dropwise addition was completed, stirring was continued for 30 minutes to mature the generated precipitate (intermediate aging step). At this time, the pH of the slurry containing the precipitate was 8.6 (step 2).
[0182] The slurry obtained in step 2 is stirred while 158.88 g of tetraethoxysilane (TEOS) with a purity of 95.0 mass% is added dropwise in the air at 30°C for 10 minutes. Stirring is then continued for 20 hours in this state to coat the precipitate with the chemical reaction product of the silicon compound (step 3). The pH of the reaction solution during the above 20 hours of stirring is 8.6. It should be noted that under this condition, the molar ratio S1 / (F+M) of the amount of Si element contained in tetraethoxysilane added to the dispersion having a pH of more than 2.0 and less than 7.0 to the amount of iron, aluminum, cobalt, and titanium ions contained in the raw material solution is 0, and the molar ratio S2 / (F+M) of the total amount of Si element contained in tetraethoxysilane added to the dispersion to the amount of iron, aluminum, cobalt, and titanium ions contained in the raw material solution is 2.84.
[0183] Thereafter, substitutional ε iron oxide magnetic particle powder was obtained by the same procedure as in Example 1. The substitutional ε iron oxide powder of Comparative Example 7 was subjected to XRD measurement, and the content of the α phase was found to be 8.7%, which was higher than that of Additional Example 2. In addition, chemical analysis of the composition, and evaluation of magnetic properties and radio wave absorption properties were performed. The measurement results are shown in Table 2.
[0184] [Comparative Example 8]
[0185] This comparative example is an experimental example of a conventional production method corresponding to the composition ratio of Example 7.
[0186] Substituted ε iron oxide magnetic particle powder was obtained by the same procedure as in Additional Comparative Example 2 except that the amounts of metal salt added were 102.73 g of an iron (III) sulfate solution having an Fe concentration of 11.65 mass% and 10.74 g of Al (III) nitrate 9-hydrate having a purity of 98%.
[0187] It should be noted that the pH of the reaction solution at the end of the addition of TEOS and the pH of the reaction solution during the above-mentioned 20 hours of stirring were both 8.6. The content of the α phase was determined by XRD measurement of the substitutional ε iron oxide magnetic particle powder involved in this comparative example, and it was 8.1%, which was higher than the value of Example 7. In addition, chemical analysis of the composition and evaluation of magnetic properties were performed. The measurement results are shown in Table 2.
[0188] [Table 1]
[0189]
[0190] [Table 2]
[0191]
Claims
1. A substitutional ε iron oxide magnetic particle powder, which is a substitutional ε iron oxide magnetic particle powder mainly comprising an ε iron-based oxide formed by substituting a part of the Fe sites of ε-Fe2O3 with other metal elements, wherein: Other metal elements that replace a part of the above-mentioned Fe site are Co, Ti and Ga. When the molar number of Fe contained in the above-mentioned substitutional ε iron oxide magnetic particle powder is set to Fe and the molar number of all metal elements that replace the Fe site is set to Me, the amount of Fe replaced by other metal elements defined by Me / (Fe+Me) is greater than 0.08 and less than 0.16, and the content of α-type iron-based oxide measured by X-ray diffraction method is less than 3%.
2. A powder compact comprising the substitutional epsilon iron oxide magnetic particle powder according to claim 1.
3. A radio wave absorber, comprising the substituted epsilon iron oxide magnetic particle powder according to claim 1 dispersed in a resin or rubber.
4. The method for producing a substitutional ε iron oxide magnetic particle powder according to claim 1, which is a method for producing a substitutional ε iron oxide magnetic particle powder mainly comprising an ε-type iron-based oxide obtained by replacing a part of the Fe sites of ε-Fe2O3 with other metal elements, comprising: A neutralization step, using an acidic aqueous solution containing trivalent iron ions and ions of a metal to replace a part of the Fe site as a raw material solution, adding a base to the raw material solution to neutralize it to a pH of 8.0 to 10.0, thereby obtaining a dispersion containing iron oxyhydroxide containing a replacing metal element, or a mixture of iron oxyhydroxide and a hydroxide of the replacing metal element; a silicon compound adding step of adding a silicon compound having a hydrolyzable group to the dispersion containing the iron oxyhydroxide containing the substitution metal element or a mixture of the iron oxyhydroxide and the hydroxide of the substitution metal element; and A aging step, wherein the dispersion liquid containing the iron oxyhydroxide containing the substitution metal element, or a mixture of the iron oxyhydroxide and the hydroxide of the substitution metal element, and the silicon compound are maintained at a pH of 8.0 to 10.0, so that the chemical reaction product of the silicon compound is coated on the iron oxyhydroxide containing the substitution metal element, or the mixture of the iron oxyhydroxide and the hydroxide of the substitution metal element; wherein, in the neutralization step, the addition of the silicon compound having a hydrolyzable group is started when the pH of the dispersion becomes 2.0 or more and 7.0 or less; When the number of moles of the silicon compound added to the dispersion having a pH of 2.0 or more and 7.0 or less is S1, the number of moles of Fe ions contained in the raw material solution is F, and the total number of moles of the replacing metal element ions is M, S1 / (F+M) is 0.01 or more and 10.0 or less, and When the total number of moles of the silicon compound added is defined as S2, S2 / (F+M) is 0.50 or more and 10.0 or less.
5. The method for producing substitutional epsilon iron oxide magnetic particle powder according to claim 4, wherein: The addition of the base in the neutralization step and the addition of the silicon compound in the silicon compound adding step are both performed continuously.
6. The method for producing substitutional epsilon iron oxide magnetic particle powder according to claim 4, wherein: The addition of the base in the neutralization step is performed continuously, and the addition of the silicon compound in the silicon compound adding step is performed intermittently.
7. The method for producing substitutional epsilon iron oxide magnetic particle powder according to claim 4, wherein: The addition of the base in the neutralization step and the addition of the silicon compound in the silicon compound addition step are both performed intermittently.
8. The method for producing substitutional epsilon iron oxide magnetic particle powder according to claim 4, wherein: The addition of the base in the neutralization step is performed intermittently, and the addition of the silicon compound in the silicon compound adding step is performed continuously.
9. A method for producing a powder compact, wherein: The substituted epsilon iron oxide magnetic particle powder according to claim 1 is compression-molded to obtain a powder compact.
Citation Information
Patent Citations
METHOD FOR PRODUCING epsilon-Fe2O3 CRYSTAL
JP2008174405A
Magnetic crystal for radio wave absorbing material and radio wave absorber
JP2008277726A
Radio wave absorption material, radio wave absorber using the same, and electromagnetic wave absorption rate measurement method
JP2009224414A
Ferrous oxide magnetic particle powder, method for manufacturing the same, coating material, and magnetic recording medium
JP2016130208A
Magnetic crystal for radio wave absorbing material and radio wave absorbent
WO2008029861A1
